7 public and private agricultural organizations in 3 Latin American countries strengthen their research and training programs on Digital Climate Smart Agriculture (D-CSA). - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
R4D carried out by the D-CSA team identified 2 problems in implementing D-CSA (i) there is a need for digital tools in agricultural organizations in order to make the best CSA decisions, and (ii) many technicians lack digital expertise. The team is strengthening digital skills in 4 agricultural organizations across LAM: INIA, FLAR, INTA, ICDF. They also built alliances with educational institutions in Colombia (EAFIT, ICESI and ITA) to prepare the next generations in digital agriculture